Pengaruh Alokasi Pajak Antar Periode Konservatisme Akuntansi Pertumbuhan Laba Terhadap Kualitas Laba - Putri, Dwi Angraeni; Hasanah, Neneng (LPPM STIE PPI, 2023)
Introduction/Main Objectives: To determine the effect of inter-period tax allocations, accounting conservatism, and profit growth on earnings quality. Background Problems: he phenomenon of the failure of financial reporting is used to fulfill the need for information on earnings quality in Indonesia. Novelty: Re-examining the quality of earnings which is the place to convey information about the quality of earnings for companies in Indonesia, especially banking sector companies listed on the IDX for 2017-2021. Research Methods: This research is quantitative in nature, and the data used is secondary data with the media in the form of financial statements of banking companies taken from www.idx.co.id and the population used in this study are banking companies listed on the IDX during the 2017 period -2021 data management using Eviews 9. Finding/Results: Inter-Period Tax Allocation, Accounting Conservatism and Profit Growth jointly or simultaneously affect Profit Quality in banking sub-sector banking companies listed on the Indonesia Stock Exchange (IDX) during 2017- 2021. Conclusion: All parties in the company should monitor each other and mutually consider various actions or policies that could have an impact on the company.